2007
DOI: 10.1080/10629360600565160
|View full text |Cite
|
Sign up to set email alerts
|

Adjusted profile likelihoods for the weibull shape parameter

Abstract: Abstract. This paper presents several different adjusted profile likelihoods for the Weibull shape parameter. These adjustments aim at reducing the impact of the nuisance parameter on the likelihood-based inference regarding the parameter of interest. Both point estimation and hypothesis testing are considered. We also show that the ratio between the estimators and the shape parameter are pivotal quantities and that the size properties of the usual and adjusted profile likelihood ratio tests depend neither on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…It is also shown that the size properties of the usual and adjusted profile likelihood ratio tests depend neither on φ nor on the value of σ set at the null hypothesis. We generalize some of the results in Ferrari et al (2005) and Yang and Xie (2003); unlike their results, ours allow for regression dependence. We also report numerical evidence on the finite-sample performance of the different inference strategies; it favors the inference obtained following Fraser and Reid (1995), Fraser et al (1999).…”
Section: S(y; η(X) σ) = Exp − Exp Y − η(X) σmentioning
confidence: 94%
See 3 more Smart Citations
“…It is also shown that the size properties of the usual and adjusted profile likelihood ratio tests depend neither on φ nor on the value of σ set at the null hypothesis. We generalize some of the results in Ferrari et al (2005) and Yang and Xie (2003); unlike their results, ours allow for regression dependence. We also report numerical evidence on the finite-sample performance of the different inference strategies; it favors the inference obtained following Fraser and Reid (1995), Fraser et al (1999).…”
Section: S(y; η(X) σ) = Exp − Exp Y − η(X) σmentioning
confidence: 94%
“…These parameterizations were obtained under noncensoring, thus it is not possible to guarantee parameter orthogonality when observations were recorded under either censoring scheme. The numerical evidences in Yang and Xie (2003) and in Ferrari et al (2005) on maximum likelihood estimation and likelihood ratio tests based on CR (β) showed that the resulting inference was reliable. In order to evaluate the effectiveness of Cox and Reid's (1987) adjustment to the Weibull profile likelihood function in the regression case, we considered parameterizations that are similar in nature to those of Yang and Xie (2003).…”
Section: Profile Likelihoods For the Weibull Shape Parametermentioning
confidence: 99%
See 2 more Smart Citations
“…In our work, we particularly consider the presence of right censorship and, in order to t this new model, we used prole methods, such as pure, adjusted and modied prole; see, for example, BarndorNielsen and McCullagh (1993), Severini (1998) and Ferrari et al (2007). Note that the pure likelihood method cannot estimate the parameters in samples with high percentages of censored points, which is what our application case showed.…”
Section: Introductionmentioning
confidence: 99%